2015
DOI: 10.1007/s10620-015-3677-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Increases Risk of Adverse Pregnancy Outcomes: A Meta-Analysis

Abstract: Inflammatory bowel disease may increase the odds of adverse pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 41 publications
1
44
0
4
Order By: Relevance
“…Medication adherence during pregnancy did not significantly influence neonatal length of stay at hospitals indicator of adverse outcomes or preterm birth for women with IBD. Correspondingly, the current literature showed no association between biologic therapy or 5‐aminosalicylates on adverse pregnancy outcomes including preterm birth, low birth weight and congenital anomalies. For thiopurine exposure during pregnancy, conflicting evidence exists .…”
Section: Discussionmentioning
confidence: 99%
“…Medication adherence during pregnancy did not significantly influence neonatal length of stay at hospitals indicator of adverse outcomes or preterm birth for women with IBD. Correspondingly, the current literature showed no association between biologic therapy or 5‐aminosalicylates on adverse pregnancy outcomes including preterm birth, low birth weight and congenital anomalies. For thiopurine exposure during pregnancy, conflicting evidence exists .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies regarding these issues have been conducted and findings on whether IBD is associated with adverse pregnancy and birth outcomes are still conflicting . Recent studies that have focused on IBD disease activity have revealed that the active disease is associated with a significant increase in adverse pregnancy and birth outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Active disease at conception has been associated with increased rates of spontaneous abortion, preterm birth (PTB), low birth weight (LBW) and congenital abnormalities (CAs). 2,4,6,7 Medical treatment is required by women with active disease during pregnancy. Anti-tumour necrosis factor α (anti-TNFα) therapy has been shown to be highly effective and is increasingly being used for the management of IBD.…”
Section: Introductionmentioning
confidence: 99%